Training Model of Pencak Silat Learning based on Android Module Design - Sinulingga, Albadi; Novita, Novita; Sagala, Ramlan Sahputera; Harahap, Adek Arifin (Budapest International Research and Critics University, 2021)
The purpose of this study was to develop a learning model for pencak silat based on android module design for junior high school (SMP) students. This research is a research and development (research and development) from Gall & Borg which is used to develop a new product. Based on the results of the evaluation analysis of pencak silat experts, media experts, physical education teacher experts, it is known that the total number of respondents' scores (∑X) is 55 and the total number of respondents' scores (∑X) is 60 so that the percentage is 91% and the criteria determined and can be determined. it is said that Providing examples of movements so that they are easy to understand meets the VALID criteria (80% - 100%) so that they can be used in the research process. It was concluded that the development of the Android module-based pencak silat drop learning model for junior high school students was very effective in learning physical education. The percentages obtained from the data analysis are 85% and 91%, respectively. This developed product aims to help improve the achievement of physical education learning objectives, especially the material for the fall of pencak silat in junior high school students. This model is made based on the level of needs of students and teachers in the movement activity of this pencak silat drop technique is still difficult to learn. The results of the second stage of the trial using this model turned out to produce 91% of the expected target, meaning that this model was effective in meeting the learning needs of pencak silat drop in junior high school students.